2021
DOI: 10.1159/000520210
|View full text |Cite
|
Sign up to set email alerts
|

Role of Different Doses of Ketamine in Postoperative Neurocognitive Function in Aged Mice Undergoing Partial Hepatectomy by Regulating the Bmal1/NMDA/NF-Κb Axis

Abstract: <b><i>Background:</i></b> The current study set out to probe the function of different doses of ketamine in postoperative neurocognitive disorder (PND) in aged mice undergoing partial hepatectomy (PH) with the involvement of the brain and muscle aryl hydrocarbon receptor nuclear translocator-like protein 1 (Bmal1)/n-methyl-D-aspartate (NMDA)/nuclear factor-kappa B (NF-κB) axis. <b><i>Methods:</i></b> First, aged mice were intraperitoneally injected with different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Wang et al found [ 23 ] that S-ketamine can reduce the level of inflammatory factors by inhibiting TLR4/NF-κB signaling pathway of microglia cells in the central nervous system of aging mice, improve neuroinflammatory response, and then relieve postoperative cognitive dysfunction. In addition, Niu et al found that [ 24 ] preoperative administration of a subanesthetic dose of ketamine activated Bmal1 mRNA expression and down-regulated the NMDA/NF-κB axis in elderly mice undergoing partial hepatectomy. And reduced inflammation, thereby alleviating postoperative cognitive decline in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al found [ 23 ] that S-ketamine can reduce the level of inflammatory factors by inhibiting TLR4/NF-κB signaling pathway of microglia cells in the central nervous system of aging mice, improve neuroinflammatory response, and then relieve postoperative cognitive dysfunction. In addition, Niu et al found that [ 24 ] preoperative administration of a subanesthetic dose of ketamine activated Bmal1 mRNA expression and down-regulated the NMDA/NF-κB axis in elderly mice undergoing partial hepatectomy. And reduced inflammation, thereby alleviating postoperative cognitive decline in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, pro-inflammatory cytokines (e.g., TNF-α and IL-1β) and NF-κB were upregulated in those brain regions enriched in activated microglia. Previous study showed that a subanesthetic dose of ketamine could activate Bmal1, downregulate the NMDA-NF-κB signaling pathway, and reduce inflammation and microglia activation in hippocampus to alleviate postoperative neurocognitive disorder (PND) in aged mice undergoing partial hepatectomy (PH) ( Niu et al, 2021 ). So far, there is no report that S-ketamine inhibits microglia activation through NF-κB signaling pathway in SPS model.…”
Section: Discussionmentioning
confidence: 99%